Порівняння використання Apache OpenWhisk та Google Cloud Functions для розроблення безсерверних застосункiв на базі Google Cloud Platform - Kondratiuk, Taras; Naumenko, Tetiana (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2021)
A comparison of using proprietary cloud platform Google Cloud Functions and open source platform Apache OpenWhisk for writing serverless applications based on the Google Cloud Platform was made. The following criteria were chosen for comparison: supported programming languages, convenience and speed of development and deployment of functions, possible ways to pass parameters to functions, options for monitoring the status of functions, speed of the cold start. As a result, main advantages and disadvantages of each platform were identified. Recommendations for use cases are given based on the features of the platforms. The results of the study can be used for further studies in the field of FaaS technologies, as there are a lot of solutions in this area that also need to be compared.